Immune checkpoint ligands expressed on mature high endothelial venules predict poor prognosis of NSCLC: have a relationship with CD8+ T lymphocytes infiltration - Luo, Jing; Shi, Xiuhuan; Liu, Yumeng; Wang, Jian; Wang, Hao; Yang, Xuena; Sun, Qian; Hui, Zhenzhen; Wei, Feng; Ren, Xiubao; Zhao, Hua (Frontiers in Immunology, 2024)
Background: An insufficient number of intratumoral CD8 + T lymphocytes is a major barrier to antitumor immunity and immunotherapy. High endothelial venules (HEVs) are the major sites through which lymphocytes enter tumors; however, the molecular mechanism through which HEVs mediate CD8 + T lymphocyte infiltration remains poorly understood.Methods: Forty-two patients with stage IIIA lung adenocarcinoma, who underwent surgery, were recruited. Multiplex immunohistochemical staining was conducted on tumor tissues to detect the immune checkpoint ligands (ICLs) expressed in the HEVs, blood vessels, and lymphatics. A new ICL score model was constructed to evaluate ligand expression. The relationship between ICL score, tumor-infiltrating CD8 + T cell frequency, and survival of patients was investigated.Results: Mature HEVs, but not blood vessels or lymphatics, mediated CD8 + T cell infiltration. However, the ICLs expressed on mature HEVs could negatively regulate CD8 + T cell entry into tertiary lymphoid structures (TLSs). In addition, according to the results obtained using our ICLtotal score model, the expression of ICLs on HEVs was observed to be a predictor of both CD8 + T cell infiltration and survival, in which a high ICLtotal score > 1 represent a weak CD8 + T cell infiltration and a high ICLtotal score > 2 predicts poor survival.Using the ICL score model, we discovered that ICLs expressed on HEVs are indicative of CD8 + T cell subset infiltration in TLSs, as well as of patient survival with lung cancer.